2013
DOI: 10.1007/s11030-013-9488-0
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the substrate scope of ugi five-center, four-component reaction U-5C-4CR): ketones as coupling partners for secondary amino acids

Abstract: Various symmetrical and unsymmetrical ketones were successfully coupled with secondary amino acids in the course of Ugi five-center, four-component reaction (U-5C-4CR), thus expanding the molecular diversity possible to be achieved by the reaction. The chemical yields depended on the degree of hindrance of the components employed and were satisfactory in view of possible steric interactions in the U-5C-4CR zwitterionic intermediate. The sense of diastereoinduction for reactions employing unsymmetrical ketones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The contemporary presence of a secondary amino group and a cyclic ketone kinetically disfavored the Ugi reaction, which did not proceed at room temperature, even with the addition of a Lewis acid as previously reported by Dawidowski for other substrates (Dawidowski et al, 2014 ). However, by performing it in a sealed tube at 65°C, a mixture of Ugi adduct 1 and cyclic imide 2 was isolated after 6 days.…”
supporting
confidence: 58%
“…The contemporary presence of a secondary amino group and a cyclic ketone kinetically disfavored the Ugi reaction, which did not proceed at room temperature, even with the addition of a Lewis acid as previously reported by Dawidowski for other substrates (Dawidowski et al, 2014 ). However, by performing it in a sealed tube at 65°C, a mixture of Ugi adduct 1 and cyclic imide 2 was isolated after 6 days.…”
supporting
confidence: 58%
“…Direct cyclization with NaOH of 83 and 86 gave directly cyclic compounds 85 and 87. NOESY spectra of cyclic compounds showed that stereochemistry was not the same for all the synthesized compounds, but depended on the structure of both the isocyanide and the ketone inputs [21].…”
Section: Scheme 17 U-5c-4cr With Histidine Yielding Diketopiperazinementioning
confidence: 95%
“…To expand the molecular diversity of Ugi 5C-4CR, various symmetrical and asymmetrical ketones were combined with secondary α-amino acids [21]. Also in this case, catalytic amounts of TiCl 4 as Lewis acid proved to increase the reaction yield.…”
Section: Ketones and Secondary α-Amino Acids In The U-5c-4cr Reactionmentioning
confidence: 99%
“…The U-5C-4CR has been recently used by Dawidowski (Dawidowski et al, 2012 ) to prepare 2,6-diketopiperazines B starting from proline as aminoacid component, exploiting an intramolecular transamidation between the primary amido group deriving from the cleavage of the tert -butyl isocyanide side-chain and the methyl ester group generated during the multicomponent step (Scheme 2 ). In our hands, when the carbonyl component of the multicomponent step was a ketone, cyclization of A to imide C partially occurred during the Ugi reaction, even on the secondary amide deriving from unhindered isocyanides (Scheme 2 ; Dawidowski et al, 2014 ). With the aim to expand the scope of this chemistry, and due to overexploited synthesis of diketopiperazine libraries for biological applications (Perrotta et al, 2001 ; Fischer, 2003 ), we envisioned the possibility to further elaborate structures C , through a set of transformations amenable to afford original scaffolds, in optically pure form, with additional reactive groups amenable of selective functionalizations.…”
Section: Introductionmentioning
confidence: 74%